High performance n-type Ag2Se film on nylon membrane for flexible thermoelectric power generator - Yufei Ding; Yang Qiu; Kefeng Cai; Qin Yao; Song Chen; Lidong Chen; Jiaqing He (Nature Communications, 2019)
Although flexible thermoelectric materials based on conducting polymers are attractive for energy harvesting, their performance is inferior to their inorganic counterparts. Here, the authors present a facile method to deliver inorganic nanowire films with high power factor and flexibility.